Sosialisasi Senam Lansia di Kelurahan Balowerti RW 6 Kota Kediri - Etika, Arif Nurma; Sulistyawati, Wiwin; Agnes, Yeni Luviana Novita; Jayani, Indah; Prasetyo, Rudi Tri; Mirasa, Yudied Agung; Yunalia, Endang Mei; Suharto, Idola Perdana Sulistyoning; Nurseskasatmata, Satria Eureka (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The elderly are vulnerable individuals, so their health needs to be improved. Knowledge of the elderly about maintaining health also needs to be improved. One way to improve the health of the elderly is through elderly exercise. The purpose of this implementation is to increase the knowledge of elderly about elderly exercise. The implementation method is divided into three stages. The first stage is to make preparations (coordination with partners, for example, caregivers), the next stage is to carry out activities (implementing counseling and simulation of elderly exercise), and the last stage is evaluation. The implementation was carried out in RW 6 Balowerti on 2-7 June 2021. This implementation was followed by 38 elderly. Based on the results, pretest were obtained almost half (47.4%) of the elderly had less knowledge levels, in the posttest it was found that most (57.9%) of the elderly had a good level of knowledge. From the results of the test, it can be concluded that there is an influence of health education and simulation of elderly exercise on the level of knowledge of the elderly.